2004
DOI: 10.1029/2003gl019359
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a recent input of magmatic gases into the quiescent volcanic edifice of Panarea, Aeolian Islands, Italy

Abstract: On 2nd/3rd November 2002, a huge amount of gas, mainly composed of CO2, was suddenly released from the sea bottom off the coast of Panarea, producing a “crater” 20 by 10 meters wide and 7 meters deep. The gas output was estimated to be 109 l/d, two orders of magnitude higher than that measured in the 1980s. The anomalous degassing rate lasted for some weeks, slowly decreasing to an almost constant rate of about 4 × 107 l/d after two months. The geo‐thermo‐barometric estimations revealed an increase of both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 11 publications
3
41
0
Order By: Relevance
“…1) is considered a quiescent volcano of the Aeolian Archipelago and shows the most intense and diffuse hydrothermal activity known since historical times. At the end of October 2002, 3 km to the East of the island near the islet of Bottaro, a low energy submarine gas eruption occurred (Caliro et al 2004;Caracausi et al 2005). In the same period, after 1 month, a paroxysmal activity (a violent eruptive manifestation of the volcano) was observed in the Stromboli Island.…”
Section: Introductionmentioning
confidence: 96%
“…1) is considered a quiescent volcano of the Aeolian Archipelago and shows the most intense and diffuse hydrothermal activity known since historical times. At the end of October 2002, 3 km to the East of the island near the islet of Bottaro, a low energy submarine gas eruption occurred (Caliro et al 2004;Caracausi et al 2005). In the same period, after 1 month, a paroxysmal activity (a violent eruptive manifestation of the volcano) was observed in the Stromboli Island.…”
Section: Introductionmentioning
confidence: 96%
“…Caliro et al (2004) reported new data obtained after the onset of the crisis, which highlighted an increase in the degassing rates by almost two orders of magnitude (about 1.8 × 10 7 mol/day on November 13th). In accordance to Caliro et al (2004) and Caracausi et al (2005), a new magmatic input would have caused the last episode of volcanic unrest, supplying a much intense feeding of magmatic fluids to the deep geothermal reservoir. As a consequence, geothermal P and T conditions increased as well as the extent of vaporization, causing the huge outgassing observed at the surface.…”
Section: Its Recent Crisesmentioning
confidence: 99%
“…The addition of magmatic gases in 2002 (Caliro et al 2004;Capaccioni et al 2007) within the hydrothermal/geothermal system induced an increase of pressure and temperature and produced the gas eruption in the Islets area (Area B), with the opening of hundreds of gas vents aligned NNE and NW trending Esposito et al 2006) and vertical crustal deformation of 4.2±0.1 cm recorded at PANA site, located at ∼2.5 km to the west, in Area A. Furthermore, about 20 low magnitude (Md≥1.0) and highfrequency seismic events occurred on November 3, 2002, between 3:37 GMT and 5:00 GMT, i.e., only a few hours before the local inhabitants of Panarea witnessed boiling sea in the surroundings of Lisca Bianca and Bottaro (Saccorotti et al 2003;Linde et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, gas eruptions of similar intensity to the 2002 eruption had not been previously observed during the last century (Mercalli 1883). Gas compositions and isotopic signatures suggested that the 2002 emissions originated from a hydrothermal/geothermal reservoir fed by seawater and magmatic fluids (Caliro et al 2004;Chiodini et al 2006;Capaccioni et al 2005Capaccioni et al , 2007. Geomorphological evidences of past phreatic explosions, such as that of November 2002, have been found in the relics of several craters on the seafloor, revealed by multibeam bathymetry , as well as by geological investigations (Esposito et al 2006).…”
Section: Introductionmentioning
confidence: 97%